Effect of phosphate‐based seed priming on strigolactone production and Striga hermonthica infection in cereals. (3rd January 2014) - Jamil, M; Charnikhova, T; Verstappen, F; Ali, Z; Wainwright, H; Bouwmeester, H J; Vurro, Maurizio
Summary Strigolactones, plant‐secreted underground signalling molecules, play an important role in agricultural ecosystems, because they mediate the interaction of crops with symbiotic AM fungi and parasitic weeds like Striga hermonthica. Cereal host plants secret these signalling molecules particularly under nutrient‐deficient conditions and especially when phosphate (P) is limiting. The objective of the present study was to see the potential of P seed priming for S. hermonthica management in cereals in relation to strigolactone production. It has been demonstrated that P fertiliser application down‐regulates the production of these signalling molecules in the rhizosphere, which results in lower S. hermonthica infection of cereals. The laboratory study showed maximum production of strigolactones from dry and water‐soaked seeds, while seed soaking in P solution reduced their production. Similarly, maximum S. hermonthica infection was observed under control treatments with dry sowing or water soaking, while P seed soaking decreased S. hermonthica germination, emergence and dry biomass in all cereal crops. Our study shows that P seed priming resulted in lower exudation of strigolactones, which induced less S. hermonthica seeds germination and hence may lead to lower S. hermonthica infection. P‐based seed priming could prove to be an effective and affordable strategy to reduce S. hermonthica infection in cereals. Further research for practical field application is needed.